Concept caring in nursing - Lenka Drahošová; Darja Jarošová (University of Ostrava, 2016)
Aim: The aim of this literature review was to search for qualitative studies focusing on the concept of caring in nursing, to analyse them and to synthesize knowledge that concerns the definition of the concept of caring in nursing from the point of view of nurses and patients. Design: Review. Methods: Qualitative studies were searched for systematically in the electronic databases Academic Search Complete (EBSCO), CINAHL, Medline, Science Direct, and the Wiley Library Online, according to set criteria and defined key words for the period 1970-2015. Seven selected articles were analysed after selection of documents with the aid of a sorting chart. Results: Nurses understand caring in nursing as a relationship with patients which is characterised on the nurses' part by an individual and empathetic approach, attentiveness, experience and sensitivity. Through caring, active communication takes place, providing information which reduces anxiety and leads to the breaking down of barriers. This relationship helps protect patients' autonomy, dignity and comfort. It requires experience on the part of nurses, and it is influenced by the environment. The nurses' personal qualities (what professional knowledge, attitudes and skills they have) and their availability, reliability, and emotional and physical support are important to patients. Conclusion: The concept of caring is a content specific interpersonal process which is characterized by the professional knowledge, skills, personal maturity, and interpersonal sensitivity of nurses, which result in the protection, emotional support, and the meeting of bio-psycho-social needs of patients. The results of the overview study could contribute to an explanation and understanding of the nature of caring as a fundamental feature of the discipline of nursing.